Methylation and Expression of Mutant FUS in Motor Neurons Differentiated From Induced Pluripotent Stem Cells From ALS Patients - Hartung, T.; Rhein, M.; Kalmbach, N.; Thau-Habermann, N.; Naujock, M.; Müschen, L.; Frieling, H.; Sterneckert, J.; Hermann, A.; Wegner, F.; Petri, S. (Frontiers in Cell and Developmental Biology, 2021)
Amyotrophic lateral sclerosis (ALS) is a rapidly progressive disease leading to degeneration of motor neurons (MNs). Epigenetic modification of gene expression is increasingly recognized as potential disease mechanism. In the present study we generated motor neurons from induced pluripotent stem cells from ALS patients carrying a mutation in the fused in sarcoma gene (FUS) and analyzed expression and promoter methylation of the FUS gene and expression of DNA methyltransferases (DNMTs) compared to healthy control cell lines. While mutant FUS neural progenitor cells (NPCs) did not show a difference in FUS and DNMT expression compared to healthy controls, differentiated mutant FUS motor neurons showed significantly lower FUS expression, higher DNMT expression and higher methylation of the proximal FUS gene promoter. Immunofluorescence revealed perceived proximity of cytoplasmic FUS aggregates in ALS MNs together with 5-methylcytosin (5-mC). Targeting disturbed methylation in ALS may therefore restore transcriptional alterations and represent a novel therapeutic strategy.